Pengolahan Limbah Kain Perca Menjadi Barang Tepat Guna (Briket, Keset, dan Tatakan Anti Panas) - Udin, Ahmad Faqih; Nopitasari, Fika Dwi; Amelia, Tri Hikmatul; Pratiwi, Tria Meriani Cahya; Ningrum, Ukma Naini Safitri Yani; Fitri, Umi Lailatul (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2023)
The convection industry, which is the economic activity of the majority of Tembok Kidul Village residents, causes an abundance of waste in the form of patchwork that has no use value and is only thrown away for free - it's not uncommon for many to even burn it to reduce the amount of patchwork waste that continues to accumulate day by day. The patchwork itself is waste that belongs to inorganic waste which undergoes a very long decomposition process, with this phenomenon the efforts of students who are carrying out KKN in the area try to make an innovation by making a product with the basic ingredients in the form of patchwork so that the leftover industrial cloth is known as As waste, it can be used to make products that have more use value. It can even become a business opportunity for people who can make good use of it and are able to read a business opportunity. The purpose of this activity is to reduce patchwork waste by making a product that can be useful in everyday life, as well as creating a business opportunity through a product-making training process carried out together with PKK mothers, with the hope that this activity can become lighter the soul of entrepreneurs in the convection sector to be able to make better use of patchwork waste to make it more useful while reducing patchwork waste to then be converted into more useful products. The method we use is community empowerment through training and mentoring by conducting outreach and joint practice of making kesed, heat-resistant mats and briquettes at regular PKK meetings. The conclusion of this activity is the empowerment of the PKK group through training in making doormats, heat-resistant mats, and briquettes from patchwork waste in the Tembok Kidul Village PKK group, Adiwerna District, Tegal Regency, namely increasing knowledge, increasing skills, and improving the attitudes of learning residents.